(untitled) (Baghdad Science Journal, 2013)
The aim of the study was comparative between oxidative stress in diabetes mellitus using the measurement of some biophysical and biochemical parameters on two groups of diabetic patients, were conducted in the Al-Yarmuk Teaching Hospital,30 patients insulin dependent diabetes mellitus (IDDM) or type 1 ,their ages ranged between (15-45) and30 patients non- insulin dependent diabetes mellitus (NIDDM) or type 2,their ages ranged between (42-65).This study has been compared with 30 healthy subjects. The present study was demonstrated to evaluate the alteration in oxidative stress as measured by plasma and red blood cells Malondialdehyde (MDA) andchanges in antioxidant mechanism as measured by plasma and red blood cells Glutathione (GSH) in patients with diabetes mellitus type 1 and type 2,in compares to healthy control group. The results showed significant increment in serum Malondialdehyde (MDA) levels ,and significant decrease in serum glutathione (GSH) levels of Diabetic patients (IDDM), (NIDDM)),compared with control. Total cholesterol (TC), triglyceride (TG) and low density lipoprotein (LDL), high density lipoprotein (HDL), Diabetic patients (IDDM),and (NIDDM)patients showed significant increases in LDL levels. LDLs and very-low-density lipoproteins (VLDLs) the so-called “bad” cholesterols. Unlike HDLs, LDLs and VLDLs are high-cholesterol particles and significant decrease in HDL compared with control Oxidative stress results when free radicals increase more than antioxidants which is naturally synthesis in the body, then causes changing in the cells accure by oxidative stress.